Оптимальная система управления технологическими процессами с порционной подачей сырьевых продуктов «ОСАУ-ПП1» - Луценко, Игорь Анатольевич; Михайленко, А. Ю.; Тытюк, В. К.; Аниськов, А. В.; Омельченко, А. В.; Гнатюк, Ю. И. (Eastern-European Journal of Enterprise Technologies, 2009)
An optimum system design for controlling technological processes with portional raw material supply is developed. The model of a firmware decision OSAC with the use of a modern technical base is given